Molecular and Immunohistochemical Biomarkers in Colorectal Carcinoma - A Single Center Study - Krsteska, Blagica; Filipovski, V; Kubelka-Sabit, K; Jasar, Dz; Velickova, N (Walter de Gruyter GmbH, 2025)
Colorectal cancer is the third most common malignancy in the world and among the most frequent causes of cancer-related death. Our study aimed to evaluate the molecular profile of the patients diagnosed with colorectal carcinoma at Clinical Hospital Acibadem-Sistina in Skopje.
Keywords: colorectal carcinoma; biomarkers; KRAS; BRAF; HER2; PDL-1